Crossing the Threshold: Ambitious Baselines for the UNFCCC New Market-Based Mechanism - Prag, Andrew (OECD/IEA Climate Change Expert Group Papers, 2012)
At COP 17 in Durban, countries defined a new market-based mechanism to promote cost-effective mitigation actions, guided by a set of principles previously agreed at COP 16. These principles include "stimulating mitigation across broad segments of the economy", "ensuring a net decrease and/or avoidance of global greenhouse gas emissions" and "assisting developed countries to meet part of their mitigation targets". This paper explores the use of ambitious crediting baselines for groups of emitters as the basis for a new market mechanism that meets the principles listed above. It focuses on how to define groups of emitters and explores different approaches for building ambition into baselines including using emissions projections and performance benchmarks. Potential elements of a process for setting baselines for subsequent international recognition are also presented. The paper builds on extensive previous analyses carried out on emissions baselines for market mechanisms, taking into account recent developments in the international negotiations